Analisis Pengaruh Process dan Physical Evidence Terhadap Minat Beli Konsumen dengan Cita Rasa sebagai Variabel Moderating - Pepy Nur Annisa; Ajat Sudrajat (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study was conducted to determine the effect of Process, Physical evidence and taste image as moderating variables that simultaneously affect consumer buying interest in Kopi Harapan Jiwa. The type of research used is a qualitative research method. used in sampling is non-probability sampling technique using quota sampling. So that the sample used is 91 respondents. The types of data used in this research are primary and secondary data. The data analysis used in this research is data quality test, classical assumption test, statistical test and multiple linear regression analysis. From the results of the research conducted, it shows that the Transformational Process variable has a significant effect on consumer buying interest, as can be seen from the t test where t count 2.595 > t table 1.991 with a significance of 0.011 < 0.05 and with a coefficient value of 0.225. This indicates that the process is a factor that affect Buying Interest. The Physical Evidence variable has a significant effect on Purchase Interest as seen from the t test where t count 7,359 > t table 1,991 with a significance of 0.000 < 0.05 and a coefficient value of 0.639. This shows that Physical Evidence can influence consumer buying interest and based on the results of moderating regression analysis shows that the taste variable cannot strengthen the influence between the price variable on buying interest and the physical evidence variable on buying interest.